Insight into the Oxygen-Sensing Mechanisms of TiO2–CeO2 Mixed Oxides Treated in a High-Energy Ball Mill: An XPS Analysis - Jelena N. Stevanović; Ana G. Silva; Nenad Bundaleski; Dana Vasiljević-Radović; Milija Sarajlić; Orlando M. N. D. Teodoro; Srđan P. Petrović (Inorganics)
This study explored the oxygen-sensing mechanism of CeO2 modified with TiO2 via high-energy ball milling at different speeds. Different characterization techniques were employed to investigate the obtained materials. Quantitative surface analysis by X-ray photoelectron spectroscopy was conducted to elucidate their sensitivity mechanisms and assess the impact of the introduction of TiO2. A comparable concentration of oxygen vacancies was found in the samples milled at 350 and 450 rpm. Electrical measurements conducted at temperatures lower than required for semiconductor gas sensors revealed the higher sensitivity of these two samples in comparison to pure CeO2 at an oxygen concentration above 10%. In contrast, the samples derived from precursors milled at the highest speed exhibited the lowest sensitivity. This may be linked to a slight decrease in the vacancy concentration and the presence of a differentially charged carbon-containing phase. Eventually, the C 1s line provided significant insight into the surface characteristics of the materials. The uniform and non-uniform charging found for pure TiO2 and CeO2, respectively, along with the high charging of CeO2, suggest that TiO2 promotes the contact between the sensing layer and the overlayer. Sensor testing showed the significantly lower resistance of mixed oxides in comparison to CeO2, which increases the utility of metal oxide-based sensors.